Between neo-extrativism and regional development. Vicuña fiber as an object of disputes in the Puna of Jujuy and Catamarca - Cowan Ros, Carlos (Universidad Nacional del Litoral, 2021)
This article contributes to the understanding of the forms of integration of peripheral regions to global production networks and their implications for regional development, through the analysis of the configuration of new productive circuits linked to vicuña fiber in the Puna of Jujuy and Catamarca. It is observed that the conception of the vicuña as a public good, in the regulatory framework, capable of being used under conservative approach, the management of silvestry and for the benefit of the Andean population configures a global production network different from others commodities and imposes obstacles to the logics of accumulation of international textile corporations. That did not prevent the the Jujuy and Catamarca productive circuits from being modelled under a neo-extractivist logic.